Applying foundation fieldbus - Mehta, B. R.; Reddy, Y. J. (International Society of Automation (ISA), 2016)
This book is a guide for the practitioners of process control systems. This book is aimed at providing the knowledge engineering and maintenance teams require. The technology benefits and areas for improvement are unbiased and from a user's point of view, bridging the gap between theory and technician-level coverage on a practical basis. The book offers a pragmatic approach to the subject based on industrial experience, taking into account the latest technologies and professional practices. Its clear coverage of concepts and applications gives engineers the knowledge they need before referring to vendor documentation, and it includes straightforward guidelines for implementing a process control system with FOUNDATION Fieldbus technology, along with some worked examples of deployments translating theory into practice. This book is an ideal introduction to the subject for junior-level professionals, as well as being an essential reference for more experienced practitioners.